2019
DOI: 10.7759/cureus.5498
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pain Scores and Medication Usage Between Three Pain Control Strategies for Pediatric Anterior Cruciate Ligament Surgery

Abstract: Introduction Assessment and management of postoperative pain in the pediatric population after anterior cruciate ligament (ACL) surgery can be challenging; the optimal approach to pain control remains controversial. Recent studies show that use of intraoperative nerve blocks may reduce the need for opioids to control pain in the postoperative period. However, it is unclear which block type is most beneficial in the pediatric outpatient setting. This study compared effectiveness of pain control among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…Of the 10 included studies, 8 11 , 12 , 14 , 20 22 , 28 , 39 were RCTs, and the other 2 were comparative studies that were designed prospectively 17 and retrospectively 30 ( Appendix Table A1 ). A total of 400 knees and 388 knees with LIA and FNB, respectively, were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 10 included studies, 8 11 , 12 , 14 , 20 22 , 28 , 39 were RCTs, and the other 2 were comparative studies that were designed prospectively 17 and retrospectively 30 ( Appendix Table A1 ). A total of 400 knees and 388 knees with LIA and FNB, respectively, were included.…”
Section: Resultsmentioning
confidence: 99%
“…Pain on VAS was evaluated at 2, 4, 8, 12, 24, and 48 hours after ACLR comparing LIA (intra-articular or periarticular injection) with FNB in included studies. At 2 hours after ACLR, 6 studies (439 patients) 11 , 12 , 20 , 21 , 30 , 39 reported VAS pain scores comparing the 2 groups, showing that the pooled MD was significantly improved in FNB compared with LIA (MD, 8.19 [95% CI, 0.75 to 15.63]; P = .03). Of the 6 studies, 5 11 , 20 , 21 , 30 , 39 reported intra-articular injection comparing FNB, showing significantly improved VAS in FNB versus intra-articular injection (MD, 8.86 [95% CI, 0.46 to 17.26]; P = .04) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…En reparación de ligamento cruzado anterior, Lisgelia et al, demostraron que el bloqueo combinado femoral+ciático es mejor que el bloqueo femoral único y la infiltración intraarticular con bupivacaína, recibiendo menos opioides en el intraoperatorio (48% vs 100% vs 98%, p < 0,0001) y posoperatorio (28% vs 92% vs 96% p < 0,0001). Además, disminuyó scores de dolor (1,5 ± 2,0 vs 4,5 ± 2,0 vs 2,8 ± 1,8, p = 0,0013) [26]. Dado el riesgo de bloqueo motor de los bloqueos de nervio femoral o ciático, se han empezado a usar bloqueos más bajos y selectivos como bloqueo del canal obturador para cirugía de rodilla o nervio ciático o poplíteo para cirugía de pie [15], [17].…”
Section: Dolor Posoperatorio En Cirugía Ambulatoria Pediátricaunclassified
“…Por ejemplo, un estudio comparó tres opciones de bloqueos analgésicos: bloqueo femoral, infiltración intra-articular con anestésico local y la combinación de bloqueo femoral con bloqueo ciático. En el grupo de pacientes con bloqueo femoral asociado a bloqueo ciático, menos del 50% requirió uso de opioides en el perioperatorio y quienes lo necesitaron, lo hicieron en dosis menores e intensidad del dolor menor (medido con EVA) que los pacientes de los otros grupos (46). Similares resultados se obtuvieron en otro estudio en que todos los pacientes recibían un bloqueo femoral continuo, pero en uno de los grupos se combinó con bloqueo ciático único.…”
Section: Bloqueos Extremidad Inferiorunclassified